Effect of intramuscular ACTH versus oral prednisolone on the developmental trajectories of children with West syndrome over 24 months: A randomised control study. (May 2021) - Sumanasena, Samanmali P.; Wanigasinghe, Jithangi; Arambepola, Carukshi; Sri Ranganathan, Shalini; Muhandiram, Eindrini
Abstract: Objective: To assess the developmental progression and compare the developmental attainments of children treated with two hormonal therapies for infantile spasms (IS) over two years (seizure and EEG outcomes of this RCT published previously). Methods: Newly diagnosed infants with IS were randomised to receive adrenocorticotrophin (ACTH) or prednisolone for 14 days. All underwent Bayley III Infant and Toddler Assessments in cognitive (Cog), receptive (RC) and expressive (EC) communication, fine (FM) and gross (GM) motor developmental subsets at baseline (T0), one-year (T1) and two-years (T2). Results: 95 infants randomised to prednisolone (n = 48) and ACTH (n = 47) groups were eligible for developmental assessments. Mean age at initial assessment was 8.75 months (SD = 6.37, range 1.46–34.4 months). 48 children presented for all three assessments. Mean composite scores of each developmental domain improved across the three time points; but the progression was significant only in relation to motor development (p = 0.04). When comparing the treatment outcomes at 2-years, mean composite scores of children treated with ACTH were significantly lower in motor domain (p = 0.023). As for developmental delay, the ACTH group (n = 32) showed significant delay in expressive communication (adjusted OR 5.46, 95% CI: 1.1, 28.57; p = 0.04) and fine motor (adjusted OR 9.4, 95% CI: 1.1, 83.3; p = 0.04) at T2 compared to the prednisolone (n = 30) in a regression analysis. Conclusion: The number of children with delay at the 2 year follow up were significantly higher in two domains in the ACTH group compared to the prednisolone group. Overall results do not show a significant advantage of ACTH over prednisolone for developmental outcomes at two years, but further comparative studies over longer periods are required for more definitive conclusions. Highlights: This clinical trial reports the developmental progression using an administered developmental assessment tool. This study showed non-significant developmental improvement of children across three time points over 2-years. Mean composite score related to motor domain was significantly lower in the ACTH group at 2-years. Proportions with expressive communication and fine motor delay were significantly higher in the ACTH group at two years. The overall findings did not show a significant advantage of ACTH versus prednisolone.